Agricultural Transformation and Human Nutrition in Africa: What has changed? - Masters, William A. (Tufts University. Tisch Library., 2017)
This presentation looks at Malthusian economics in Africa and how food consumption relates to population. It also looks at spending on agriculture in contrast to national income.; Keywords: food diversity, Malthusian economics, Africa, population, agricultural spending, national income, Tufts University.; NIL Presentations, 2016.; Feed the Future Innovation Lab for Nutrition, USAID Contract No. AID-OAA-L-10-000006, managed by Tufts University's Gerald J. & Dorothy R. Friedman School of Nutrition Science and Policy